2017
DOI: 10.1002/zaac.201700229
|View full text |Cite
|
Sign up to set email alerts
|

Methanesulfonamide in Superacids: Investigations of the CH3 SO2 NH3 + Cation

Abstract: The preparation of protonated methanesulfonamide was carried out using the superacidic systems HF/AsF5 and HF/SbF5. The vibrational spectroscopic characterization was supported by quantum chemical calculations performed with the PBE1PBE method using the 6‐311G++(3df, 3pd) basis set. A remarkable long nitrogen–sulfur bond length of 1.804(6) Å was observed in a single‐crystal X‐ray structure analysis of [CH3SO2NH3]+[Sb2F11]–. It crystallizes in the orthorhombic space group P21/c with four formula units in the un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 16 publications
2
2
0
Order By: Relevance
“…With a Sb1−F5−Sb2 bond angle of 140.7(1)°, the Sb 2 F 11 − anion possesses an angulated conformation. All these bond lengths, as well as the angles are in accordance with previously reported Sb 2 F 11 − anions [21,22] …”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…With a Sb1−F5−Sb2 bond angle of 140.7(1)°, the Sb 2 F 11 − anion possesses an angulated conformation. All these bond lengths, as well as the angles are in accordance with previously reported Sb 2 F 11 − anions [21,22] …”
Section: Resultssupporting
confidence: 91%
“…All these bond lengths, as well as the angles are in accordance with previously reported Sb 2 F 11 À anions. [21,22] Theoretical Calculations…”
Section: Synthesis Of [Cmentioning
confidence: 99%
“…In these studies protonations at the nitrogen site are indicated, which is in agreement with a theoretical study where it was confirmed that the nitrogen site is favorable to the protonation . In a previous study methanesulfonamide was investigated in the superacidic systems HF/ M F 5 ( M = As, Sb) . It was found that the protonation takes place selectively at the nitrogen atom.…”
Section: Introductionsupporting
confidence: 88%
“…[8] In a previous study methanesulfonamide was investigated in the superacidic systems HF/MF 5 (M = As, Sb). [9] It was found that the protonation takes place selectively at the nitrogen atom.…”
Section: Introductionmentioning
confidence: 99%